Noah’s Inebriated Curse (Gen 9:20–27) - Schlimm, Matthew Richard (2025)
Genesis 9:20-27 raises difficult exegetical questions, such as why Noah curses Canaan rather than Ham in 9:25-27. Additionally, the text has an infamous history of providing a popular defense of slavery in Africa and the United States. Some African American interpreters have argued that Noah’s curse should not be understood as divinely sanctioned words because Noah is still under the influence of alcohol when he speaks. Linking Noah’s actions in Gen 9:20-24 with his words in 9:25-27, these interpreters attend to the literary context of Noah’s speech while also combatting one of the most noxious uses of the Bible in recent centuries. This article adds exegetical support to this approach, demonstrating how this interpretation avoids the pitfalls of other treatments while working exceptionally well on a literary level with the passage itself. All of Noah’s behaviors in 9:21-27 align with clinical descriptions of alcohol intoxication.
Keywords: Genesis; Ham; Noah; blessing and cursing; Drunkenness; Racism; Slavery